Dynamic performance of displacement ventilation in a lecture hall. Issue 3 (8th December 2021) - Lastovets, Natalia; Sirén, Kai; Kosonen, Risto; Jokisalo, Juha; Kilpeläinen, Simo
Abstract: An accurate temperature gradient calculation is essential for displacement ventilation (DV) system design since it directly relates to thecalculation of the required supply airflow rate. Inaccurate temperature prediction can cause poor thermal comfort and wrong sizing of the ventilation and cooling systems. A heat balance-based method is usually applied in displacement ventilation (DV) design when overheating is the primary indoor climate concern. The temperature gradient in DV systems is usually calculated with lumped-parameter nodal models. Several simplified nodal models were developed and implemented in the various building simulation software to estimate the temperature stratification in rooms with DV. Recent studies reveal that the multi-nodal models provide the most accurate temperature gradient prediction. However, the majority of dynamic calculation methods assumes either complete mixing of zone air or linearised temperature gradient. The present study introduces the dynamic temperature gradient model for DV and investigates the effect of thermal mass on the temperature stratification. The model was validated with the experimental results of a lecture room with displacement ventilation. The room air temperature measurements were conducted during three weeks at 20 different heights. The supply air temperature and occupancy rate were recorded during each scheduled lecture. The developed dynamic nodal model is able to calculate the air temperatures in the occupied zone accurately. The effect of the thermal mass and changing heat gains on the room air temperature stratification is analysed for the lecture room with DV.